Effectiveness of Modified Truth or Dare Game in Improving Toxicology Knowledge of Workers at Tofu Factory X - Nursucilowati, Luvi Lia; Tianisa, Berliana Noor; Putri, Risa Anggita; Febriananda, Hanif Satria; Ananto, Favian Anggorokasih Putra; Kartika, Nada Rahmadina (Journal of Safety Education, 2024)
There are 84,000 tofu producers in Indonesia, ranging from household industries with 5-8 workers to medium-sized industries with 50-100 workers. In a single tofu production process, additional chemicals such as CH3COOH and MgSO4 are used. These conditions pose potential safety and health hazards for workers, requiring control measures. This study employs a quantitative approach, using an experimental model with treatment in the form of a card game. Data was collected using primary data methods, such as questionnaire instruments and direct field observation. The questionnaire was compiled based on priority hazard assessment using HIRADC calculations and then tested for validity and reliability. The questionnaire results were tested using the Wilcoxon Signed Rank Test because the data were not normally distributed. The study results for worker respondents (0.027) and the public (0.000), or P value < 0.05, indicate that H0 is rejected, and Ha is accepted. The modified truth-or-dare card game method was found to have a significant impact on toxicology knowledge among workers and the general public.